The mediating role of intergroup anxiety in the relationship between meta-stereotype and achievement motive among adolescents in rural–urban integration areas: a cross-sectional study - Chuanyong Guo; Chuanyong Guo; Mingying Li; Limin Hou (Frontiers in Psychology)
BackgroundAdolescence is a crucial period for identity formation and the development of achievement motivation. In the context of rural–urban integration, adolescents encounter diverse social, cultural, and economic dynamics, which complicate their developmental processes through intergroup relations and perceptions. Meta-stereotypes represent a key factor that influences adolescent motivation and behavior. This study aims to examine the mediating role of intergroup anxiety in the relationship between meta-stereotypes and achievement motivation among adolescents in rural–urban integration areas.MethodsThis cross-sectional study included 396 adolescents (aged 12–15 years; mean age = 13.89, SD = 0.98; 48.74% female) from a middle school in the rural–urban integration area. Participants completed self-report measures assessing intergroup anxiety, achievement motivation, and meta-stereotype activation. A mediation analysis with a bias-corrected bootstrapping procedure (5,000 draws) was conducted to assess whether intergroup anxiety mediates the relationship between meta-stereotypes and achievement motivation.ResultsAchievement motivation was negatively correlated with meta-stereotypes (r = −0.12, p = 0.009), age (r = −0.13, p = 0.004), years of education (r = −0.14, p = 0.002), and intergroup anxiety (r = −0.30, p < 0.001). Intergroup anxiety was positively correlated with meta-stereotypes (r = 0.22, p < 0.001) and sex (r = 0.08, p = 0.047). Across all participants, meta-stereotype activation significantly increased intergroup anxiety (p < 0.001) and significantly decreased achievement motivation (p = 0.019). Rural adolescents exhibited the same pattern, while urban adolescents did not show significant changes. The 95% bootstrap confidence interval for the indirect effect of intergroup anxiety was [−0.201, −0.065], indicating a significant mediation effect. Subgroup analysis revealed no mediating effect among urban adolescents, while rural adolescents demonstrated significant partial mediation by intergroup anxiety on both the motivation to approach success and the motivation to avoid failure.ConclusionThis study explored the interplay among meta-stereotypes, intergroup anxiety, and achievement motivation in adolescents from rural–urban integration areas in China. The findings offer important insights for educational strategies and psychological interventions aimed at enhancing interpersonal relationships and academic confidence among rural adolescents in these areas.